Multi-donor multi-course faecal microbiota transplantation relieves the symptoms of chronic hemorrhagic radiation proctitis: A case report. Issue 39 (25th September 2020) - Zheng, Ya-Mei; He, Xing-Xiang; Xia, Harry Hua-Xiang; Yuan, Yu; Xie, Wen-Rui; Cai, Jie-Yi; Xu, Jia-Ting; Wu, Li-Hao
Abstract: Rationale: There are many treatments for chronic hemorrhagic radiation colorectal inflammation, but only a few treatments are supported by high-quality research evidence. Studies have shown that the occurrence and development of radiation proctitis are closely associated with the intestinal flora. Animal studies have indicated that faecal microbiota transplantation (FMT) can improve radiation enteropathy in a mouse model. Patient concerns: A 45-year-old female patient suffered from recurrent hematochezia and diarrhea for half a year after radiotherapy and underwent recurrent transfusion treatments. Colonoscopy showed obvious congestion of the sigmoid colon and rectal mucosa, a smooth surface, and bleeding that was easily induced by touch, which are consistent with radiation proctitis. The pathological findings revealed chronic mucosal inflammation. The magnetic resonance imaging examination of the pelvic cavity with a plain scan and enhancement showed changes after radiotherapy and chemotherapy, and no obvious tumor recurrence or metastasis was found. The laboratory examinations excluded pathogen infection. Diagnoses: Based on the history and examinations, the final diagnosis of this patient was chronic hemorrhagic radiation proctitis. Interventions: The patient was treated with a total of 4 individual courses of FMT. Outcomes: After the six-month follow-up, her hematochezia, abdominal pain and diarrhea were relieved. Furthermore, 16S rRNA sequencing of the feces showed that the intestinal bacterial composition of the patient obviously changed after FMT and became similar to that of the donors. Lessons: This case report shows that FMT can relieve the symptoms of hematochezia and diarrhea by changing the bacterial community structure in patients with chronic hemorrhagic radiation proctitis.